2012
DOI: 10.1371/journal.pone.0038352
|View full text |Cite
|
Sign up to set email alerts
|

Persistently Elevated Right Ventricular Index of Myocardial Performance in Preterm Infants with Incipient Bronchopulmonary Dysplasia

Abstract: ObjectivesElevated pulmonary vascular resistance occurs during the first days after birth in all newborn infants and persists in infants at risk for bronchopulmonary dysplasia (BPD).It is difficult to measure in a non-invasive fashion. We assessed the usefulness of the right ventricular index of myocardial performance (RIMP) to estimate pulmonary vascular resistance in very low birth weight infants.Study DesignProspective echocardiography on day of life (DOL) 2, 7, 14, and 28 in 121 preterm infants (median [qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 32 publications
8
63
2
Order By: Relevance
“…These values are lower compared to those obtained in our study (RVMPI = 0.47 ± 0.23). Nevertheless, we confirmed the results obtained by Czernik et al [2] after PDA closure (RVMPI = 0.32 ± 0.08 on the 7 th DOL), and those obtained on the 28 th DOL (RVMPI = 0.31 ± 0.10). Similarly to Czernik et al [2], we observed increased RVMPI (0.31 ± 0.1) values on the 28 th DOL in BPD sufferers diagnosed at 36 weeks PCA, compared to the mild BPD (0.22 ± 0.06) and healthy term neonates (0.23 ± 0.1).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…These values are lower compared to those obtained in our study (RVMPI = 0.47 ± 0.23). Nevertheless, we confirmed the results obtained by Czernik et al [2] after PDA closure (RVMPI = 0.32 ± 0.08 on the 7 th DOL), and those obtained on the 28 th DOL (RVMPI = 0.31 ± 0.10). Similarly to Czernik et al [2], we observed increased RVMPI (0.31 ± 0.1) values on the 28 th DOL in BPD sufferers diagnosed at 36 weeks PCA, compared to the mild BPD (0.22 ± 0.06) and healthy term neonates (0.23 ± 0.1).…”
Section: Resultssupporting
confidence: 93%
“…Nevertheless, we confirmed the results obtained by Czernik et al [2] after PDA closure (RVMPI = 0.32 ± 0.08 on the 7 th DOL), and those obtained on the 28 th DOL (RVMPI = 0.31 ± 0.10). Similarly to Czernik et al [2], we observed increased RVMPI (0.31 ± 0.1) values on the 28 th DOL in BPD sufferers diagnosed at 36 weeks PCA, compared to the mild BPD (0.22 ± 0.06) and healthy term neonates (0.23 ± 0.1). Such elevated RVMPI values in children with severe BPD reflect a persistently elevated pressure in the pulmonary circulation, resulting from a lower number of blood vessels surrounding the pulmonary alveoli, hypertrophy of the vessel media, muscularisation of small peripheral vessels, and inappropriate vasoreactivity [2].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The myocardial performance index (or Tei index), a marker of ventricular dysfunction consisting of the sum of isovolumetric contraction and relaxation times divided by the ejection time, is elevated in primary PH, may be elevated in preterm infants with BPD, and may correlate with BPD severity. [79][80][81][82] More recently, tissue Doppler measurements have been found to correlate with elevated end diastolic pressure in adults. The ratio of the early Doppler inflow velocity to the early myocardial tissue Doppler velocity (E/E¢) has been shown to correlate with the severity of BPD, but requires further study to determine if it will be a useful marker of disease.…”
Section: Screening and Diagnosis Of Ph In Bpdmentioning
confidence: 99%